The Mahatma Ghandi Memorial - (:unkn) unknown (Y. De Lima and Co. Ltd., Trinidad, 2010)
This memorial to Mahatma Gandhi is at the centre of San Fernando on Harris Promenade. Mahatma Ghandi was a great civil leader of India whose work and techniques of peaceful civil disobedience have been an inspiration to people worldwide. The memorial consists of a bronze statue brought from India and erected in 1952 to a solid pedestal that is first rectangular then square and bears an inscription on the front. The monument stands at least 5 meters (15 feet) high. It shows Gandhi in stride. The monument is fenced around with iron chains that hang from concrete posts. Behind the monument are historic buildings such as: the St. Joseph’s Convent and the San Fernando Police Station, which went up in flames in February 2009 and were reported then to be about 140 years old. Postcard number K-6270.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Monuments--Trinidad and Tobago; Memorials--Trinidad and Tobago; Statues--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--San Fernando; Buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; High schools--Trinidad and Tobago; Catholic high schools--Trinidad and Tobago